#TITLE_ALTERNATIVE# - OCTOVA (NIM : 223 09 005), ADREE
A tunnel with a dual function was built in Kuala Lumpur Malaysia to solving flood and traffic congestion problem. Construction of the tunnel must has good element of safety and environmental impact. Therefore, in the construction of the tunnel should be done several studies to make sure the tunnel that made has a high level of safety. One of them is subsurface imaging of rock structures. Travel time cross-hole seismic tomography is applied to describing the structure of the subsurface. The sources are placed at one borehole and some receivers are placed in the others. First arrival travel time data that received by each receiver is used as the input data in seismic tomography method. This research is devided into three steps. The first step is reconstructing the synthetic model based on field parameters. Field parameters are divided into 24 receivers and 45 receivers. The second step is applying inversion process for the field data that consists of five pairs bore holes. The last step is testing quality of tomogram with resolution test. Data processing using FAST software produces an explicit shape and resemble the initial model reconstruction of synthetic model with 45 receivers. The tomography processing in field data indicates cavities in several place between the bore holes. Cavities are identified on BH2A-BH1, BH4A-BH2A and BH4A-BH5 with elongated and rounded structure. In resolution tests using a checker-board, anomalies still can be identified up to 2 meter x 2 meter size. Travel time cross-hole seismic tomography analysis proves this mothod is very good to describing subsurface structure and boundary layer. Size and anomalies position can be recognized and interpreted easily.